Haematology, serum biochemistry and mineral profiles of Trinket cattle, an endangered feral cattle associated with the colonial history of Nicobar - DE, A K; PERUMAL, P; GEORGE, Z; MONDAL, S; MUNISWAMY, K; SAWHNEY, S; RAVI, S K; KUNDU, A; KUNDU, M S; BHATTACHARYA, D (The Indian Journal of Animal Sciences, 2021)
Trinket cattle is a highly endangered feral cattle of Trinket Island, linked with the colonial history of Andaman and Nicobar Islands. Danish people during their colonial time introduced these cattle in Trinket Island. Great Sumatra earthquake and Indian Ocean Tsunami in 2004 has forced these cattle to become feral in nature. Due to negligence, the cattle is at the brink of extinction and only around 150 of descendants of the cattle are reported. In the present study, the haematology, serum biochemistry and mineral profiles of Trinket cattle were evaluated. Study indicated that all the values were under the normal physiological range. These findings of this study may serve as reference values in which alterations due to metabolic, nutrient deficiency, physiological and health status can be compared for diagnostic and therapeutic purpose.